2020
DOI: 10.1080/24694452.2020.1807900
|View full text |Cite
|
Sign up to set email alerts
|

Webs of Care: Qualitative GIS Research on Aging, Mobility, and Care Relations in Singapore

Abstract: The connections between time and space have been studied considerably in quantitative and qualitative research on the geographies of care; however, researchers tend to prioritize one approach over the other. Our article integrates analyses of activity spaces and space-time paths with conceptualizations of care developed in qualitative studies to deepen understanding of the spatiotemporal care routines of older adults in Singapore. Using qualitative geographic information systems (QualiGIS), we develop a compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Power argues that treating the assembly of these components as housing assemblages ‘opens up a conceptualisation of domestic caring that is political and social rather than individual, autonomous and private’ (Power, 2019: 769). In Ho et al (2021), the authors compare the care assemblages of citizen and immigrant older adults to show how differences in legal statuses and social networks impact each group’s capacity to negotiate the spatio-temporal constraints they face in managing self, peer and intergenerational care. Combining assemblage theory with GIS analysis, Ho et al trouble the fixity of models of activity spaces to argue that capacities to care can be made more resilient through state provisions for flexible care arrangements.…”
Section: Assemblagesmentioning
confidence: 99%
“…Power argues that treating the assembly of these components as housing assemblages ‘opens up a conceptualisation of domestic caring that is political and social rather than individual, autonomous and private’ (Power, 2019: 769). In Ho et al (2021), the authors compare the care assemblages of citizen and immigrant older adults to show how differences in legal statuses and social networks impact each group’s capacity to negotiate the spatio-temporal constraints they face in managing self, peer and intergenerational care. Combining assemblage theory with GIS analysis, Ho et al trouble the fixity of models of activity spaces to argue that capacities to care can be made more resilient through state provisions for flexible care arrangements.…”
Section: Assemblagesmentioning
confidence: 99%
“…Building on earlier work on caringscapes (Bowlby, 2012), social geographers are now capturing even more complex constellations of space-time by analytically approaching examining care as assemblages (Power, 2019; Price-Robertson and Duff, 2019). Such approaches examine the way heterogeneous components of care work are drawn into relation with one another, including how family and non-familial carers are enfolded into webs of care through their relational and interdependent temporalities (Ho et al, 2020). Domestic rhythms and routines of social reproduction require collaboration and coordination, revealing inequalities of time use and ‘the social, spatial and technological assemblages that structure and maintain these’ (Holdsworth, 2020: 5).…”
Section: Intimate Space-times Life Stage and Life-coursementioning
confidence: 99%
“…Although older age is often associated with slowing down after retirement and as frailty advances, older adults in fact enact new activity rhythms. Ho et al (2020), for example, demonstrate how both older men and women in Singapore develop new post-retirement routines that involve not only grandparenting duties but also ‘active ageing’ activities to delay the onset of frailty later in the life-course. Focusing on the intersection of ageing and masculinity among retired British farmers, Riley (2020) observes that diurnal rhythms and certain spaces in the home (e.g.…”
Section: Intimate Space-times Life Stage and Life-coursementioning
confidence: 99%
“…Many public health researchers have found that visualisation of the spatial distribution of health-related events of target populations and making informed public health decisions faster are the two primary applications of GIS data/methods in health-related studies 25 28 29. The applications of GIS methodologies in older adults’ care and research are growing,30–32 however, there is limited research on GIS in assessing recruitment strategies among older adults with and without dementia 33 34…”
Section: Introductionmentioning
confidence: 99%